RANCANG BANGUN APLIKASI PENGELOLAAN BISNIS IKLAN PADA PT. JAWA POS KORAN SURABAYA - Triamukti, M. Adam; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Advertising is the most revenue from print media business Jawa Pos. Problems advertising that appears in part because the process of advertising is difficult for customers, ad management processes that complicate the internal parts of Jawa Pos and the provision of related management report ads that are less informative and not realtime. Resulting in decreased customer number of 7% to 10% every day.In order to overcome problems related to the management of the ads created ad business management applications. Applications are made to facilitate customers in conducting advertising, simplify internal parts Jawa Pos managing the advertising and providing information or reports in realtime that is easily understood by management.The test results indicate that the advertising business management application created to solve the problems of business management advertising Jawa Pos. With the online advertising services on an ad management application, it can help enable customers to place an ad. Then with their online ad management services that connect customers, layout and traffic officer orders the advertising management process can be easily done. In addition to the provision of services online reports, the management can easily access and monitor the development of the advertising business Jawa Pos.